A revision of tetrapod footprints from the late Carboniferous of the West Midlands, UK - Luke E. Meade; Andrew S. Jones; Richard J. Butler (PeerJ, 2016)
A series of sandstone slabs from Hamstead, Birmingham (West Midlands, UK), preserve an assemblage of tetrapod trackways and individual tracks from the Enville Member of the Salop Formation (late Carboniferous: late Moscovian–Kasimovian). This material has received limited previous study, despite being one of the few British sites to preserve Carboniferous tetrapod footprints. Here, we restudy and revise the taxonomy of this material, and document it using 3D models produced using photogrammetry. The assemblage is dominated by large tracks assigned to Limnopus isp., which were made by early amphibians (temnospondyls). A number of similar but smaller tracks are assigned to Batrachichnus salamandroides (also made by temnospondyls). Dimetropus leisnerianus (made by early synapsids) and Dromopus lacertoides (made by lizard-like sauropsids such as araeoscelids) are also present. This ichnofauna contrasts with a slightly stratigraphically older, more extensive and better-studied assemblage from Alveley (Shropshire), which is dominated by small amphibians with relatively rare reptiliomorphs, but which lacks Dromopus tracks. The presence of Dromopus lacertoides at Hamstead is consistent with the trend towards increasing aridity through the late Carboniferous. It is possible that the assemblage is the stratigraphically oldest occurrence of this important amniote ichnotaxon.